Makna Sarkasme dalam Kolom Komentar Akun Tiktok @puttriipadang (Padriani Putri) : Kajian Pragmatik - Sari, Hefi Nopita (Lembaga Teewan Journal Solutions, 2026)
he problem statement in this research is how the implied meaning of sarcasm is found in the comment section of the TikTok account @puttriipadang. The aim of this study is to describe the types of sarcasm and to understand the meanings contained in the comments on the TikTok account @puttriipadang. This research uses a qualitative analysis method. The data collection techniques used are observation, note-taking, and documentation. The data analysis techniques are carried out by classifying the data, analyzing, describing, and concluding. The data source in this study consists of comments containing sarcastic meanings on the TikTok account @puttriipadang. The data were obtained by observing the comments, recording the data, taking screenshots, and analyzing the meaning of sarcasm. Based on the results of the study, several types of sarcasm were found in the comment section of the TikTok account @puttriipadang, namely propositional sarcasm, lexical sarcasm, prefix-based sarcasm, and illocutionary sarcasm. There were 20 data points of propositional sarcasm, 14 data points of lexical sarcasm, 10 data points of prefix-based sarcasm, and 11 data points of illocutionary sarcasm. These forms of sarcasm are used by social media users to mock, ridicule, and deliver indirect criticism. In addition, the meaning of sarcasm in the comments also shows that comments may appear positive but actually carry negative meanings in the form of ridicule or satire. The total number of data found in this study is 55.